Analysis Strategy Visibility And Activity At The Website Stikom.edu In Terms Of Increasing Ranked Webometrics - Metta Ameilia Damayanti; Anjik Sukmaaji; Sri Suhandiah (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Stikom Surabaya has a main website stikom.edu who became participants of webometrics. Webometrics is one of increased us based website on the internet which is used as a reference against the institution, then the visibility and activity. Cybermetrics lab publishes a ranking of universities every 6 months once in January and July. Stikom Surabaya following webometrics from 2012 and ranked 73 which was release in January 2016, after analyzed Stikom Surabaya decline rank on the website stikom.edu, then the required visibility strategy analysis and activity on the website stikom.edu in the webometrics ranking improvement efforts. The analysis is done using Web Impact Factor to measure the average number of links. The analysis is done generating strategies to increase ranking webometrics. The resulting strategy there are 4 categories were needed, namely, policy, technical, content or content and supporting or supporters. The resulting strategy is 12 new strategies to increase visibility/impact and 17 strategies to increase activity. The strategy can be done by planning time during 6 months from the last issued webometrics ranking and systematically.